Penerapan Iman Kristen Yang Berpusat Pada Buah-Buah Roh Berdasarkan Galatia 5:22-23 (International Forum of Researchers and Lecturers, 2025)
This article examines the application of the Christian faith by focusing on the development of the fruits of the Spirit as recorded in Galatians 5:22-23. Through an analysis of the biblical text, this article explains how the Fruits of the Spirit are not just the ultimate goal but a continuous transformation and this article discusses the spiritual growth that is realized through the development of the Fruits of the Spirit. Explain how the Fruits of the Spirit are in the context of a society where there are many conflicts that are very influential in the growth of our spiritual faith. The development of the Fruits of the Spirit significantly contributes to the formation of a healthy and adaptive Christian character. The study also highlights the practical implications for self-development for believers.